Labor market power in developing countries: Evidence from colombian plants (2021)
How much can employers in low and middle-income countries suppress wages below marginal productivity? Using plant and customs data from Colombia, we exploit predetermined variation across plants in sales export destination combined with variation in exchange rates to generate plant-specific shocks to marginal revenue productivity and labor demand. We estimate a firm-level labor supply elasticity of around 2.5, implying that workers produce about 40% more than their wage level. Our results indicate that Colombian and US manufacturers have a comparable degree of labor market power.